2017
DOI: 10.1111/head.13184
|View full text |Cite
|
Sign up to set email alerts
|

Electronic‐Diary for Recording Headaches, Triggers, and Medication Use: Development and Evaluation

Abstract: The e-diaries evaluated in this research would prove a useful tool in clinical trials of behavioral treatment for headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…Headache diaries are the gold standard for assessing headache frequency and other daily headache‐related parameters. Short paper‐and‐pencil or electronic headache diaries as used in the present study have good reliability and validity 19 …”
Section: Methodsmentioning
confidence: 73%
“…Headache diaries are the gold standard for assessing headache frequency and other daily headache‐related parameters. Short paper‐and‐pencil or electronic headache diaries as used in the present study have good reliability and validity 19 …”
Section: Methodsmentioning
confidence: 73%
“…Data related to the comparative acceptability of each pain assessment modality were collected in 60% (32/53) studies [ 5 , 7 , 21 , 22 , 24 - 27 , 29 , 30 , 34 , 36 , 38 - 42 , 47 - 53 , 56 , 57 , 60 , 61 , 63 , 64 , 66 , 69 , 72 ]. Overall, electronic programs to assess pain are highly acceptable to patients.…”
Section: Resultsmentioning
confidence: 99%
“…One study (4%) found no difference in participant satisfaction between electronic and conventional pain instruments [ 47 ]. Nine studies did not ask patients to specifically declare a preference for assessment modality but still reported high patient satisfaction with the electronic method [ 5 , 7 , 27 , 29 , 48 , 52 , 53 , 56 , 64 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies employed telemedicine equipment or computer programs dedicated to telemedicine 19,20,21 . Smartphone technology has been used for headache diaries, behavioral interventions, and electronic monitoring of headaches 22,23,24,25 . Digital technology has the advantage of facilitating information registry, thus enabling the creation of large databases.…”
Section: Discussionmentioning
confidence: 99%